Pessoas surdas em uma escola regular de ensinofundamental: acesso e inclusão - Lins, Lívia Maria Montenegro (2020)
The eductional scenery that considers inclusion policies for deaf people, tends to take into account, what the school may understand as a language barrier, namely, between deaf people, and those with normal auditory sense. As a matter of fact, the paths though which the schools have followed for this inclusion may take place, are based on this purpose in the vast majority. This research has been developed, to take an investigative look to find out how the inclusion process is done by regular schools, in order to desnaturalize the dominant technical patterns proposed for the education of deaf people. his research has as locus Municipal Elementary school situated in Joao Pessoa city, which is considerated as a reference in the inclusion of desabled people in 2009. Therefore, all the problem issues which this survey has been developed were: what are the adopted procedures for the inclusion of deaf people at a school which is considered as a reference in Joao Pessoa city? What methodological theoretical elements guide the school curriculum? Actually, the general objective is to analyse the inclusion of deaf people at a regular school which is considered as reference for this purpose. It is important to emphasize , a main precept , regarding to the education of deaf people with reflexions that come to propose new looks, recognizing the alternity as valuable tools in this way of thinking. Further developed the following specific objectives: Reflect on the inclusion of the implemented model at the school in question. Identify the pedagogical theoritical elements guiding the Political Pedagogical Project (PPP) of inclusion that supports the school curriculum and reflects on the activities developed by the teachers. It is a qualitative approach survey, whose production of the empirical material took place in two stages; namely, semi structured with male and female educators working at the investigated school, anchored under the lens of cultural studies of education. The sdudy seeks to develop reflexions which are present in the dominant rules, regarding to education of deaf people that pass through looks, recognizing alternity as a valuable tool of the way of thinking.